Indigenous peoples, higher education and affirmative action at UFAM - Oliveira Menezes, Reinaldo (2021)
This paper aims to discuss the current issue of indigenous access to the Federal University of Amazonas and their permanence, through Affirmative Action, in undergraduate courses. Thus, this work is qualitative in nature, based on bibliographic and documentary research. It aims to contextualize and understand the process of construction and materialization of the right to education for indigenous peoples. In synthesis, affirmative action in contemporary times has been of paramount importance, both for access and for the permanence of indigenous peoples in higher education, restoring inequalities in higher education.